Bioconversão energética da folha e bagaço de mandioca pelo fungo Rhizopus oligosporus para obtenção de alimento funcional - Miranda, Juliane Cristina [UNESP] (2014)
The increasing world population and the growing demand for food, generates lots of organic residues such as leaf (FFM) and bagasse (FBM) cassava (Manhit esculenta Crantz), where the leaf is discarded in the field and bagasse is a sold residue from the extraction of starch. An alternative to adding value to these residues is the biotransformation using microorganisms. The objective of this work was to promote protein bioconversion of leaf and cassava bagasse by the fungus Rhizopus oligosporus by solid state fermentation and evaluate the contribution of NPK fertilizer on fermentation and the parameters analyzed...